Rancang Bangun dan Evaluasi Sistem Pelacakan Lokasi Antarpendaki Berbasis LoRa dengan Aplikasi Android Tanpa Koneksi Internet - mahfudi, isa; Delila Lukisani Tungga Dewi; Hadiwiyatno (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2025)
Mountain hiking activities in Indonesia continue to grow, yet limited cellular network coverage in mountainous areas remains a major challenge for communication and hiker safety monitoring. This study aims to design and implement a LoRa-based hiker location tracking system integrated with an Android application operating without an internet connection. The system consists of ESP32-based nodes integrated with GPS SIM808 and LoRa Ebyte E220-900T22D modules for transmitting positional data between devices. The coordinates are exchanged via a peer-to-peer (P2P) LoRa network and displayed in real-time on an Android application using offline OpenStreetMap. The research employed a Research and Development (R&D) approach through stages of system design, implementation, and functional testing in open-field conditions. Experimental results show that the system achieved an average GPS accuracy deviation of 6–7 meters, LoRa communication range of up to 500 meters (LOS) and 350 meters (NLOS), and an average Bluetooth communication delay of 990 ms. The findings demonstrate that the proposed system can effectively display inter-hiker positions in near real-time without internet connectivity, enhancing safety and coordination among hikers in signal-limited environments.